2020
DOI: 10.1073/pnas.1919264117
|View full text |Cite
|
Sign up to set email alerts
|

Functional lipid pairs as building blocks of phase-separated membranes

Abstract: Biological membranes exhibit a great deal of compositional and phase heterogeneity due to hundreds of chemically distinct components. As a result, phase separation processes in cell membranes are extremely difficult to study, especially at the molecular level. It is currently believed that the lateral membrane heterogeneity and the formation of domains, or rafts, are driven by lipid–lipid and lipid–protein interactions. Nevertheless, the underlying mechanisms regulating membrane heterogeneity remain poorly und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 76 publications
1
15
0
1
Order By: Relevance
“…The absolute affinities of different membrane phospholipids for cholesterol are not known, but it has been shown that they vary over about an order of magnitude 2,21‐24 . Their complexes have stoichiometries that range from 1:1 for high‐affinity (long chain, saturated) species to two phospholipids per cholesterol for less avid lipids 3,18,20,23,25 . Sterols are more avid for sphingomyelin than for glycerophospholipids, and they favor saturated over unsaturated chains and phosphorylcholine over phosphorylserine over phosphorylethanolamine polar head groups.…”
Section: Cholesterol Complexes With Phospholipidsmentioning
confidence: 99%
“…The absolute affinities of different membrane phospholipids for cholesterol are not known, but it has been shown that they vary over about an order of magnitude 2,21‐24 . Their complexes have stoichiometries that range from 1:1 for high‐affinity (long chain, saturated) species to two phospholipids per cholesterol for less avid lipids 3,18,20,23,25 . Sterols are more avid for sphingomyelin than for glycerophospholipids, and they favor saturated over unsaturated chains and phosphorylcholine over phosphorylserine over phosphorylethanolamine polar head groups.…”
Section: Cholesterol Complexes With Phospholipidsmentioning
confidence: 99%
“…On the other hand, the addition of even a small amount of cholesterol to the membrane brings about the formation of domains in it [13], whose thickness is larger than the thickness of single component membrane [20]. The arrangement of the domains around the BR molecules reduces the local difference between the thicknesses of the hydrophobic part of protein and the membrane, thus reducing the strength of the lipid-protein interaction (Fig.…”
Section: Results and Their Discussionmentioning
confidence: 99%
“…Lipid membranes are an important component of living organisms, because they regulate plenty of the processes that are required to maintain the viability of every cell and cell organelles. That is why a considerable number of works on biophysics is devoted to the study of phase transitions in lipid membranes and their dependence on the temperature and pressure [1][2][3][4], the structural characteristics of various lipid phases [5,6], the influence of various impurities on the properties of membranes [7][8][9][10][11], as well as to the measurement of the dynamic characteristics of singleand multicomponent membranes [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…However, recent research has suggested that sphingomyelin also has strong homophilic interactions, and that cholesterol's interactions take place deeper within the membrane's acyl chain region, i.e., lower than sphingomyelin's functional amide group ( Yano et al, 2018 ). Moreover, in systems that form large domains, there is evidence of cholesterol segregating within ordered domains ( Javanainen et al, 2017 , Soloviov et al, 2020 ). Currently, it is safe to say that cholesterol's role within ordered domains remains a topic of current research and debate.…”
Section: Lipid Interactions In Domain Formationmentioning
confidence: 99%